The Consequences of Corona Virus on Human Rights System - Malla Khater, Maya Hasan (Journal of Economic, Administrative and Legal Sciences, 2020)
The outbreak of the New Corona Epidemic has been leading governments around the world to adopt strategies to limit its spread and to counter it. Some of the measures taken have affected a number of fundamental rights and freedoms, which are guaranteed according to the international human rights law, and not just intended the right of life and the right of effective health care. In fact, many other rights were affected intentionally or unintentionally. This study seeks to highlight on states practices and responses related to fighting against the Corona Crisis, its impact on human rights in general, and the rights of the most vulnerable groups in particular, by using the descriptive and analytical method. One of the most important results of this research is that the protection of human rights while combating this Epidemic can’t be considered as a secondary issue. It is necessary for these government measures to be consistent with the rules and provisions of the International Human Rights Law.